Histopathological Effects Of 4g And 5g Electromagnetic Radiations On Liver Tissue - Haroon, Arifa; Ali, Shabana; Umar, Ubaid; Farooq, Sadia; Fahad, Tayyaba; Qureshi, Tayyaba (Journal of Rawalpindi Medical College, 2025)
Objective: To compare the effect of EMF at 2100 MHz and 3500 MHz on the histomorphology and functions of a rat’s liver. Methods: Thirty male Sprague Dawley rats were divided into three groups with 10 rats in each group: a control group with no EMF exposure, a 2100 MHz exposure group, and a 3500 MHz exposure group. The rats in the exposure groups were subjected to EMF for 5h/day for 4 weeks. Histological examinations were performed to observe sinusoidal dilatation, congestion, and hepatocyte vacuolation in the classic hepatic lobule. Serum LFTS were assessed to evaluate liver function. Results: The control group of rats exhibited no hepatocyte vacuolation, and only 10% showed sinusoidal dilatation and congestion. In contrast, 40% of the rats in Group B displayed moderate sinusoidal dilatation and congestion, whereas Group C had 20% with severe and 60% with moderate sinusoidal dilatation and congestion. Severe hepatocyte vacuolation was observed in 10% of the rats in Group C, while Group B had no rats with severe hepatocyte vacuolation. When comparing serum levels among the groups, ALT levels were 35.5 ± 4.7 in Group A (control), 42.4 ± 3.9 in Group B, and 49.8 ± 4.5 in Group C. Likewise, AST levels were 140.6 ± 4.3 in Group A, 263.5 ± 5.1 in Group B, and 295.3 ± 4.6 in Group C. Conclusion: Electromagnetic field (EMF) exposure at frequencies of 2100 MHz and 3500 MHz has been found to impair liver structure and function in rats, with the severity of damage increasing with frequency. This indicates that higher frequencies, such as those used in 5G networks, may pose greater risks. This study underscores the potential risks associated with EMF exposure and indicates that further research is necessary to grasp its impact on human health.